2008
DOI: 10.1097/paf.0b013e3181847dfc
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Unexpected Death Related to Medullary Brain Lesions

Abstract: The sudden unexpected death of a person believed healthy has occasionally been followed by a detailed postmortem examination that revealed no cause of death except for the unexpected presence of a medullary brain lesion. Our review of all available cases of sudden unexpected death related to medullary brain lesions (SUD-MBL) revealed the absence of any specific constellation of ante-mortem disease characteristics, together with the finding that major motor and sensory pathways were grossly preserved in most ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…In situations of heightened demand due to seizures (Blumenfeld et al, 2004), even relatively short phases of hypoxemia could then lead to additional damage in vulnerable regions, e.g. the watershed area that encompasses the solitary tract nucleus (Jaster et al, 2008; De Caro et al, 2000; Lorin de la Grandmaison et al, 2001; Sarnat et al, 2004), and so not only aggravate the existing damage but also cause additional damage in hitherto unaffected brainstem regions (mechanism 2). Over time the damage caused by such seizure-related hypoxic episodes could accumulate and ultimately become severe enough to lead to the type of complete breakdown of the autonomic control in a situation of heightened demand that seems to be the hallmark of SUDEP (Jaster et al, 2008; Ryvelin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations of heightened demand due to seizures (Blumenfeld et al, 2004), even relatively short phases of hypoxemia could then lead to additional damage in vulnerable regions, e.g. the watershed area that encompasses the solitary tract nucleus (Jaster et al, 2008; De Caro et al, 2000; Lorin de la Grandmaison et al, 2001; Sarnat et al, 2004), and so not only aggravate the existing damage but also cause additional damage in hitherto unaffected brainstem regions (mechanism 2). Over time the damage caused by such seizure-related hypoxic episodes could accumulate and ultimately become severe enough to lead to the type of complete breakdown of the autonomic control in a situation of heightened demand that seems to be the hallmark of SUDEP (Jaster et al, 2008; Ryvelin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…the watershed area that encompasses the solitary tract nucleus (Jaster et al, 2008; De Caro et al, 2000; Lorin de la Grandmaison et al, 2001; Sarnat et al, 2004), and so not only aggravate the existing damage but also cause additional damage in hitherto unaffected brainstem regions (mechanism 2). Over time the damage caused by such seizure-related hypoxic episodes could accumulate and ultimately become severe enough to lead to the type of complete breakdown of the autonomic control in a situation of heightened demand that seems to be the hallmark of SUDEP (Jaster et al, 2008; Ryvelin et al, 2013). This scenario indicates that this seizure related lesion in the dorsal mesencephalon, if it affects structures involved in autonomic control, could be sufficient to pose a risk factor for SUDEP.…”
Section: Discussionmentioning
confidence: 99%
“…This explains sudden death from snake bites [321,322], vaccines [323][324][325][326][327][328][329][330][331][332][333], and cocaine [215], in otherwise healthy people, as examples. Depending on their surfactant property and their position within the Hofmeister series, environmental biological or chemical intoxicants of virtually any type can provide the EIWS to induce SDS.…”
Section: Discussionmentioning
confidence: 99%
“…[11516172327293133] The postmortem studies in patients with SUD attributed to the craniocervical junction disorders have identified a variety of medullary lesions as the only apparent cause of death. [1617] The most notable finding shared by the majority of these cases has been gross preservation of motor and sensory pathways, suggesting that a defect in the brainstem autonomic cardiorespiratory centers and inability of these centers to respond to typical homeostatic stress plays an important role in the etiopathology of sudden death associated with craniocervical junction disorders. [1415] Automatic respiration control, predominantly during sleep, depends on the activity of chemoreceptive neurons that respond to hypoxia, hypercapnia, and pH in the blood and cerebrospinal fluid (CSF) and is chemically regulated by both peripheral chemoreceptors and chemosensitive centers within the medulla.…”
Section: Discussionmentioning
confidence: 99%
“…[3821] Thus, the victims of neurogenic SUD and neurogenic SUND, due to the preservation of motor and sensory pathways and relatively normal ventilatory response, are generally considered healthy with no or minimal neurological signs prior to their event. [381621] Nevertheless, ongoing compromises of autonomic centers in the brainstem related to the nonspecific structural lesions of the craniocervical junction can lead to a wide variety of autonomic disturbances including emesis, cardiorespiratory problems, sleep apnea, sudden death, and death during sleep. [48141621] Short and long-term opioid use is also associated with several potential adverse effects and toxicities, including respiratory depression and sleep-related breathing disorders, predominantly central sleep apnea.…”
Section: Discussionmentioning
confidence: 99%